The Convergence of Intellectual Property Protection for Local Bags : A Study on Design Similarities with Well Known-Brands Through the Regimes of Trademark, Industrial Design, and Geographical Indication - Fakhira, Regita; Dirkareshza, Rianda (Journal of Law, Politic and Humanities, 2025)
The local bag industry faces significant challenges in protecting Intellectual Property Rights (IPR) due to design similarities with well-known brands, which are closely related to the sustainability of the national economy. This study aims to analyze the convergence of trademark, industrial design, and geographical indication protections within the local bag industry and to identify solutions to address design-similarity issues. This research employs a normative juridical method, complemented by a literature review and in-depth interviews with experts from the Directorate General of Intellectual Property, drawing on statutory, conceptual, and sociological approaches. The findings indicate that the convergence of IPR protection across these three regimes provides complementary safeguards that strengthen the legal position of local bag products and enhance their competitiveness in the global market. However, its effectiveness remains constrained by low awareness of IPR registration, high registration costs, and weak law enforcement. Through this layered protection framework, local bag entrepreneurs can gain stronger protection, promote innovation, and reinforce the economic and cultural values unique to Indonesia, thereby contributing to the development of the national creative economy.